THE EFFECT OF DRTA AND KWL STRATEGIES ON STUDENTS' READING COMPREHENSION SKILLS IN TERMS OF THEIR READING INTEREST - Anggi Citra Apriliana (IKIP Siliwangi, 2022)
AbstractThis study is aimed at obtaining a comprehensive picture of the effect of DRTA and KWL strategies on reading comprehension ability in terms of students' reading interest. The background of this research is the low interest and ability of students in understanding the content of reading materials. The sample in this study are fourth grade students at Kananga Elementary School, Jatinangor District, Sumedang Regency. The method used is Factoral Design Two Factor Experiment. The instruments used are reading comprehension test and reading interest questionnaire. The results of the study can be explained as follows: 1) The use of DRTA and KWL strategies are categorized as quite effective, which can be seen from the N-Gain test scores of 64.02% and 64.97%. 2) Based on the Test of Between Subject Effect output, the sig value is 0.424 > 0.05, which can be concluded that there is no significant difference between reading comprehension skills in terms of students' reading interest. It means that students' reading interest has no effect on reading comprehension ability. Students who have low reading interest do not necessarily have low reading skills, and vice versa. 3) The calculation of the two-way ANOVA regarding the interaction effect between reading strategies and reading interest on reading comprehension ability, obtained a sig value of 0.026 < 0.05, which can be concluded that there is an interaction effect between learning strategies and reading interest on improving students' reading comprehension skills. Keywords: Reading Comprehension, DRTA, KWL, Students’ Reading InterestAbstrakTujuan penelitian ini adalah untuk memperoleh gambaran secara komprehensif mengenai pengaruh strategi DRTA dan KWL terhadap kemampuan membaca pemahaman ditinjau dari minat baca siswa. Latar belakang penelitian ini yaitu rendahnya minat dan kemampuan siswa dalam memahami isi bacaan. Sampel dalam penelitian ini adalah siswa kelas IV SDN Kananga Kecamatan Jatinangor Kabupaten Sumedang. Metode yang digunakan adalah eksperimen dengan desain faktorial 2 x 2 (Factorial Design Two Factor Experiment). Instrumen yang digunakan yaitu tes kemampuan membaca pemahaman dan angket minat baca. Hasil penelitian dapat dijelaskan sebagai berikut: 1) Penggunaan strategi DRTA dan KWL termasuk ke dalam kategori cukup efektif hal ini terbukti dari hasil pengujian N-Gain Score sebesar 64,02% dan 64,97%. 2) Berdasarkan hasil output Test of Between Subject Effect diperoleh nilai sig sebesar 0,424 ˃ 0,05 sehingga dapat disimpulkan bahwa tidak ada perbedaan yang signifikan antara kemampuan membaca pemahaman ditinjau dari minat baca siswa. Artinya, minat baca siswa tidak berpengaruh terhadap kemampuan membaca pemahaman. Siswa yang memiliki minat baca rendah belum tentu memiliki kemampuan membaca rendah begitupun sebaliknya, siswa yang memiliki minat baca tinggi belum tentu memiliki kemampuan membaca pemahaman tinggi. 3) Berdasarkan penghitungan two ways annova mengenai efek interaksi antara strategi membaca dan minat baca terhadap kemampuan membaca pemahaman, diperoleh nilai sig sebesar 0,026 ˂ 0,05, maka dapat disimpulkan bahwa terdapat efek interaksi antara strategi pembelajaran dan minat baca terhadap peningkatan kemampuan membaca pemahaman siswa. Kata Kunci: Membaca Pemahaman, DRTA, KWL, Minat Baca Siswa